Ethnobotany of wild edible plants used by local communities in three districts along the upper Bengawan Solo River, Central Java, Indonesia - ADITYA TRIYANTO; FITRIA PURNAMASARI; FENINTA SETYANING PARAMITA; FAUZAN RAFI WICAKSONO; FARIE AIMAR RAMADHAN; SUGENG BUDIHARTA; SURAPON SAENSOUK; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Triyanto A, Purnamasari F, Paramita FS, Wicaksono FR, Ramadhan FA, Budiharta S, Saensouk S, Setyawan AD. 2024. Ethnobotany of wild edible plants used by local communities in three districts along the upper Bengawan Solo River, Central Java, Indonesia. Biodiversitas 25: 1596-1605. Wild Edible Plants (WEPs) grow naturally in the environment without human assistance and have parts that humans or animals can consume. The declining interest of local communities in consumable wild plant species, especially among the younger generation, resulted in the loss of public knowledge on the utilization of wild natural resources and the extinction of various types of wild species in nature. This study aims to determine wild edible plants used by local communities in three districts along the Bengawan Solo River, Central Java, Indonesia. This research used qualitative and quantitative data obtained by conducting open, semi-structured, and structured interviews with 90 respondents aged 20-80 years old. Quantitative data was analyzed to produce Use Values (UV) and Informant Consensus Factor (ICF). The study found that the community consumes approximately 49 species from 32 families of WEPs and the most consumed species were Leucaena leucocephala, Carica papaya, Dendrocalamus asper, Muntingia calabura, Peperomia pellucida, Gnetum gnemon, Moringa oleifera, and Portulaca oleracea. Consumable wild plants along the Bengawan Solo River have an ICF value ranging from 0.645 to 1. The WEPs were used for carbohydrates, vegetables, fruits, seeds, and medicine. The study highlights the diverse uses of plant parts, emphasizing the community's holistic approach to incorporating wild plants into their diet and medicine. The research emphasizes the need to preserve and comprehend the multifaceted roles of WEPs, which are crucial for sustaining cultural traditions and community well-being.